KOMUNIKASI ANTARBUDAYA ETNIS LOKAL DENGAN ETNIS PENDATANG : STUDI PADA MAHASISWA/I FAKULTAS ADAB DAN ILMU BUDAYA UIN SUNAN KALIJAGA YOGYAKARTA - Saputra, Eko (Interaksi: Jurnal Ilmu Komunikasi, 2019)
This study examines the behaviors, interactions and acculturation of intercultural communication with students Faculty of Adab dan Ilmu Budaya at the Sunan Kalijaga State Islamic University in Yogyakarta (UIN-SUKA).  Intercultural communication for new students at the Faculty Adab dan Ilmu Budaya UIN-SUKA has been become an annual tradition for them to get to know each other, learn and understand the cultural characteristics of their respective faculty friends.  In this paper, the author am willing explore the intercultural communication of local ethnicities with ethnic migrants in the Faculty of Adab and Ilmu Budaya at UIN-SUKA which covers the introduction, adaptation, symbolic interactionalism and cultural accuracy. Answer these various questions, the author made a qualitative methodological approach by conducting interviews and interlocutor to some of the Faculty of Adab dan Ilmu Budaya UIN-SUKA of Culture students. The results of this study show that their intercultural communication is very intensive to their friends who are of different cultures.  They communicate between their cultures in classrooms, halls, lobbies, canteens, seats, and campus grounds.  Then, it is not uncommon for them to do intercultural collaboration at certain events, for example Pekan Budya, Disaster Care Students, and Social Solidarity. The contribution of this study is to provide readers with literature about intercultural communication with new students who have cultural differences, because every year new students experience the same case.